2020
DOI: 10.5194/amt-2020-328
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An improved method for atmospheric <sup>14</sup>CO measurements

Abstract: Abstract. Important uncertainties remain in our understanding of the spatial and temporal variability of atmospheric hydroxyl radical concentration ([OH]). Carbon-14-containing carbon monoxide (14CO) is a useful tracer that can help in the characterization of [OH] variability. Prior measurements of atmospheric 14CO concentration ([14CO] are limited in both their spatial and temporal extent, partly due to the very large air sample volumes that have been required for measurements (500–1000 liters at standard tem… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Adding the larger uncertainty of the biogenic fraction estimation of 2%, gives a combined uncertainty that is below the variability of 14 CO in most air masses (remote SH air showed the least variability) during a typical 1-hr air sample collection period using a high-pressure compressor. Recently, Petrenko et al (2021) reported an air sample collection and processing method for much smaller air samples, namely less than 100 L. This avoids the use of high-pressure sample air cylinders, which are more expensive and time consuming to transport from the point of collection to the laboratory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding the larger uncertainty of the biogenic fraction estimation of 2%, gives a combined uncertainty that is below the variability of 14 CO in most air masses (remote SH air showed the least variability) during a typical 1-hr air sample collection period using a high-pressure compressor. Recently, Petrenko et al (2021) reported an air sample collection and processing method for much smaller air samples, namely less than 100 L. This avoids the use of high-pressure sample air cylinders, which are more expensive and time consuming to transport from the point of collection to the laboratory.…”
Section: Resultsmentioning
confidence: 99%
“…14 CO has a source that is probably not affected noticeably by industrial emissions, it is a geophysical tracer. From this point of view is stands to reason to continue 14 CO observations, and indeed recently further improvements were just reported (Petrenko et al 2021). Current atmospheric chemistry models are of great complexity and the reconstructed rate of removal of trace gases by OH remains an essential piece of output.…”
Section: Discussionmentioning
confidence: 96%
“…However, to better characterize the effects from the addition of extraneous C during the graphitization process, we used a linear empirical correction from 10 commensurately-sized 14 C standards and blanks at ANSTO (see Supplementary Materials, Fig. S2A, 265 Table S7) following Petrenko et al (2021). This approach has the benefit of bracketing the effects of extraneous C from graphitization at ANSTO with low and high 14 C standards, similar to the approach for the 14 CH4 samples.…”
Section: Large Volume Samples For 14 Co and 14 Ch4 Measurements 225mentioning
confidence: 99%